Alcoholismo y depresión en estudiantes universitarios. Ambato, 2019 - Jorge Luis, León Andrade (2020)
The objective of this research work is to analyze the levels of alcoholism and depression in students who attend the Directorate of University Welfare at the Technical University of Ambato. It has a non-experimental descriptive design and quantitative approach in which the levels of alcoholism and depression can be identified in students who attend at the University Welfare Directorate. The sample that corresponds to 39 students to whom the following psychological batteries were applied: the AUDIT test for alcoholism and the BECK test for depression, which were evaluated by the members of the University Welfare Directorate and have a reliability of the 90% on your results. Regarding the results obtained, it could be seen that 23% of those surveyed present a No Risk Consumption, 38.5% a dependence on alcoholism, while in depression obtains the following results 43.6% a mínimum of moderate depression and 0% a severe depression. From obtaining these results regarding alcohol consumption, a psychological intervention plan was proposed because the indicators are high in risky consumption and alcohol dependence.